Choosing the exchange rate regime – a case for intermediate regimes for emerging and developing economies - Jurek, Michał (Economics and Business Review, 2018)
The main objective of the paper is to verify the vanishing interim regime hypothesis (so-called bipolar view) and to analyse factors that may influence the probability of use of intermediate exchange rate regimes, especially in emerging and developing economies. In order to accomplish the research objectives the evolution of exchange rate regimes is presented with the special consideration of decisions of IMF member states in this respect. Next a logistic regression model that estimates the probability of use of an intermediate regime is applied. The results achieved allow a challenge to the vanishing interim regime hypothesis. Empirical observations support this hypothesis only in advanced countries and not in their emerging and developing peers.